The corporate social responsibility strategies and practices of South African organisations - Fredericksz, Lara Anne (My University, 2015)
Corporate Social Responsibility (CSR) has become a strategic business and marketing tool for businesses worldwide which, if integrated into an organisation’s overall marketing and business strategy, can lead to increased financial returns, a favourable reputation, a more productive workforce and a greater competitive advantage. Unfortunately however, CSR is not always fully understood or practiced in the precise manner that would benefit organisations in these ways. In this case it can be suggested that these organisations have adopted a CSR strategy as an afterthought that is “bolted on” and not strategically aligned or “built in” to their business. In order to assess whether CSR strategies are built in or bolted on within a South African market context, the perceptions of employees were investigated to assess how well CSR is being integrated within South African organisations. Not only are employee CSR perceptions a relatively unexplored dimension of CSR but employees are one of the most important stakeholders within any organisation and thus clear and consistent communication to them relating to their CSR strategy will contribute towards ensuring that it is aligned and consistent with the overall business direction. To evaluate employee perceptions, a questionnaire was developed and adapted from previous CSR studies and administered to employees working for South African organisations. Pre-requisites for candidates to be able to participate in this study included employment in a South African company that employs a CSR programme or CSI measures, and who work within the main head office of their organisation. A total of 196 respondents were analysed. The areas of focus included linkage of CSR to organisational vision, mission and values; culture; involvement of the CEO; CSR communication and CSR linked to job satisfaction and organisational trust. The research findings show that there are a number of gaps in the fundamental involvement with CSR and the communication of CSR to employees as well as linkage to core business aspects. Areas where South African organisations need to focus their efforts to ensure that CSR is built in or more entrenched within their business include engaging employees in more CSR activities, aligning company culture closer to CSR, improving internal CSR communication and finally focusing on improving CSR dimensions which are linked to job satisfaction and organisational trust.
Thesis (M.M. (Strategic Marketing))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Business Administration, 2015.